2002
DOI: 10.1093/intimm/dxf020
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for CD69 in thymocyte emigration

Abstract: The early activation marker, CD69, is transiently expressed on activated mature T cells and on thymocytes that are undergoing positive or negative selection in the thymus. CD69 is a member of the NK gene complex family of C-type lectin-like signaling receptors; however, its function is unknown. In this report, we describe the characterization of mice that constitutively express high levels of surface CD69 on immature and mature T cells throughout development. Constitutive surface expression of CD69 did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 35 publications
8
111
0
2
Order By: Relevance
“…CD69 is an antagonist of S1PR1, blocking the S1P‐mediated egress of lymphocytes from secondary lymphoid organs into the blood 140, 141, 142. It is remarkable that in CD69 + memory T cells of bone marrow, S1PR1 expression is blocked on the level of transcription, since it has also been reported that CD69 can directly block surface expression of S1PR1 143.…”
Section: The Lifestyle Of Bone Marrow Memory T Lymphocytesmentioning
confidence: 99%
“…CD69 is an antagonist of S1PR1, blocking the S1P‐mediated egress of lymphocytes from secondary lymphoid organs into the blood 140, 141, 142. It is remarkable that in CD69 + memory T cells of bone marrow, S1PR1 expression is blocked on the level of transcription, since it has also been reported that CD69 can directly block surface expression of S1PR1 143.…”
Section: The Lifestyle Of Bone Marrow Memory T Lymphocytesmentioning
confidence: 99%
“…Another agonist-independent mechanism for modulation of S1P 1 receptor surface expression is the observed direct interaction of S1P 1 with CD69, which prevents cell surface expression of both molecules when co-expressed (41). Transgenic expression of CD69 in T cells led to accumulation of mature T cells in thymus (42), resembling a similar phenotype to S1P 1 receptor deficiency (1, 4) and FTY720 treatment (43). PKC inhibition also leads to S1P 1 receptor down-regulation, and FTY720 itself is a potent PKC inhibitor (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…CD69 is an early activation marker that is transiently expressed on activated mature T cells. Although its function remains to be fully elucidated, a recent study based on CD69 transgenic mice suggest a role in the regulation of T cell trafficking [21]. In particular, CD69 expression prevented cells from migrating.…”
Section: Discussionmentioning
confidence: 99%